Presence and Absence of the Tomb Owner in Wall Scenes and Funerary Models - Barker, Georgia 19XX- (Zeitschrift für ägyptische Sprache und Altertumskunde, 2023)
The tomb owner’s figure dominates scenes displayed on elite tomb-chapel walls, forming an essential part of the medium’s repertoire. Yet among funerary models, the tomb owner rarely appears. While the two artistic media exhibit many similarities in design, their representation of the tomb owner forms one of several distinguishing features that are rarely acknowledged. This paper examines the presence and absence of the tomb owner in wall scenes and funerary models from the Old and Middle Kingdom periods. It is here proposed that this difference in representation can be explained by the two artistic media’s contrasting technical properties and location in the tomb.